205k views
4 votes
Help me ASAP plz I'm stuck at this​

Help me ASAP plz I'm stuck at this​-example-1
User ThinkFloyd
by
4.7k points

2 Answers

2 votes

Answer:

Substitute the 2nd and 3rd equations for x and y into the first equation.

Use the distributive property to simplify terms

Combine like terms to get 12z = -24

Solve for z = -2

Solve for x and Y by substituting z into 2nd and 3rd equations

Explanation:

2x - y + 3z = -12

x = 3 + 2z

y = -6 - 5z

Substitute;

2(3 + 2z) - (-6 - 5z) + 3z = -12

Distribute;

6 + 4z + 6 + 5z + 3z = -12

Combine like terms;

12 + 12z = -12

Subtract 12 from both sides;

12z = -24

Divide by 12 to get z;

z = -2

Substitute z into x and y to get their values;

x = 3 + 2(-2)

x = 3 - 4

x = -1

y = -6 - 5(-2)

y = -6 + 10

y = 4

Now to check;

2x - y + 3z = -12

2(-1) - (4) + 3(-2) = -12

-2 - 4 - 6 = -12

-12 = -12

CORRECT!

User Alonso Dominguez
by
5.2k points
6 votes

Answer:

b

Explanation:

because its math and it makes sense

User Jacobbaer
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.